Parasitisasi Telenomus sp. dalam Menekan Populasi Telur Spodoptera frugiperda (Lepidoptera: Noctuidae) pada Tanaman Jagung - Indah Wulan Suci; Shakeilla Aretha Zelika; Amarisya Shafa Luzia; Rilwa Wallingga; M Al-Fatih Abdurrosyid; Chandra Irsan (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Suci IW, Zelika SA, Luzia AS, Wallingga R, Abdurrosyid MA, Irsan C. 2021. Parasitisation of Telenomus sp. on suppressing Spodoptera frugiperda's (Lepidoptera: Noctuidae) egg population on the maize plant. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 689-696. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Spodoptera frugiperda (Lepidoptera: Noctuidae) is a polyphagous pest which attack plantation plant, one of them is maize plant (Zea mays). Attact aftermath this pest which was mentioned as Fall Armyworm which can injured the farmer products cause of its behaviour which attack growing point plant until can trigger failure of leaf preening. One of how to control S. frugiperda pest is by relying on natural enemic, which is parasitoid. Telenomus sp. is the one of many species of egg parasitoids of Fall Armyworm S. frugiperda, which is used most of the biodegradable control to reduce specific pest attacks on maize plants. The role of parasitoid is also important in suppressing host populations because they are specific and easier to breed than other natural enemies such as predators and fungi. The aimed of this scientific papers was to knew the potential and level of parasitism of Telenomus sp. on S. frugiperda’s egg population. The method used for this scientific papers was studied of literature from book and scientific journal on internet. Based on studied of literature, the parasitic rate of S. frugiperda’s eggs when the female imago of Telenomus sp. parasitize 50 S. frugiperda’s eggs succesfully parasitized 35 of the 50 S. frugiperda’s eggs or equivalent to 69.40%. As the S. frugiperda’s egg that has been parasitized by the Telenomus sp. parasitoid hatch, the number of females produced from the S. frugiperda host reached 74% and the number of male offspring was only 26%. An analysis of the Telenomus sp. parasitic levels on the S. frugiperda’s egg can be an important factor in biodiversity control and have high potential for controlling egg population of S. frugiperda on the maize plant. Surely this study can help the farmer in decreasing use of pesticides or another dangerous chemicals.